From Digital HRM to ESG Performance: A Micro to Macro Framework of Green HRM, Work Engagement, and Employee Green Behavior - Lokesh Tomar; Salil Seth (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2026)
Digital transformation and sustainability have become central to contemporary organizational strategy, increasing the need to understand how technological systems support measurable Environmental, Social, and Governance (ESG) performance. Although Digital Human Resource Management (Digital HRM) and Green Human Resource Management (GHRM) have received growing scholarly attention, research integrating digital HR infrastructures with sustainability-oriented HR practices and employee-level outcomes remains limited. This study develops an integrated conceptual framework linking Digital Human Resource Management, Green Human Resource Management, green work engagement, employee green behavior, and ESG performance. Grounded in the Ability-Motivation-Opportunity (AMO) theory, the framework proposes a sequential mechanism through which digitally enabled HR systems institutionalize green HR practices, enhance employee engagement with environmental objectives, stimulate pro-environmental workplace behavior, and ultimately contribute to organizational ESG performance. By advancing a micro-to-macro explanation of digitally supported sustainability implementation, the study bridges digital transformation and green HRM research and clarifies the behavioral foundations of ESG outcomes. The proposed model provides a structured basis for future empirical examination of digitally enabled sustainable organizational performance.